Enhancing Antibacterial Activity Against Escherichia coli K-12 of Peptide Ib-AMP4 with Synthetic Analogues - Flórez Castillo, J. M. (2014)
A family of Ib-AMP4 peptide analogues was obtained by solid phase synthesis, modifying the net charge and hydrophobicity of C-terminal domain by replacing certain amino acidic residues by arginine and tryptophan. Additionally, disulfide bonds were eliminated by replacing the cysteine residues by methionine, which resulted in a decrease in the number of synthesis byproducts, and consequently diminished the subsequent purification steps. The obtained peptides were purified by RP-HPLC and their molecular mass was determined by MALDI-TOF mass spectrometry. The peptide analogues (IC50 between 1 and 50 μM) presented a higher antibacterial activity against Escherichia coli K-12 than the native peptide (IC50 > 100 μM). The hemolytic activity of the peptide with the highest antibacterial efficacy presented no degradation of erythrocytes for a concentration of 1 μM that corresponds to its IC50 value. The results show that the synthesized peptides are good candidates for the treatment of diseases caused by E. coli.